2008
DOI: 10.1098/rsbl.2007.0578
|View full text |Cite
|
Sign up to set email alerts
|

No postcopulatory response to inbreeding by male crickets

Abstract: Previous studies of the cricket Teleogryllus oceanicus have shown a paternity bias towards non-sibling males. Although non-kin-biased paternity could represent a mechanism of postcopulatory inbreeding avoidance by females, evolutionarily stable strategy (ESS) models of ejaculate evolution also predict that males should reduce their expenditure on the ejaculate when mating with their sisters. Here we provide a test of these models, finding that male crickets invest equally in matings with full-siblings, half-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…, 2008). In T. oceanicus , although males and females appear to differ in their post‐copulatory responses to inbreeding (Simmons & Thomas, 2008), our study provides evidence of male precopulatory inbreeding avoidance through preferential matings with conspecifics that are more genetically dissimilar. Our study therefore highlights the importance of considering not only both pre‐ and post‐copulatory mechanisms but also male selectivity as a confounding variable in studies investigating female mate choice and inbreeding avoidance.…”
Section: Discussionmentioning
confidence: 72%
“…, 2008). In T. oceanicus , although males and females appear to differ in their post‐copulatory responses to inbreeding (Simmons & Thomas, 2008), our study provides evidence of male precopulatory inbreeding avoidance through preferential matings with conspecifics that are more genetically dissimilar. Our study therefore highlights the importance of considering not only both pre‐ and post‐copulatory mechanisms but also male selectivity as a confounding variable in studies investigating female mate choice and inbreeding avoidance.…”
Section: Discussionmentioning
confidence: 72%
“…However, empirical studies have provided conflicting evidence for the ability of males to alter their reproductive effort based on female relatedness (Pizzari et al . ; Simmons & Thomas ; Lewis & Wedell ). Moreover, inbreeding avoidance strategies are more likely to evolve in the sex that endures the greatest cost (Zeh & Zeh ).…”
Section: Introductionmentioning
confidence: 99%
“…When males recognise that mating with kin is unavoidable, it has been suggested that they might adopt a peri-copulatory strategy to offset the cost of inbreeding, for example, by tailoring the ejaculate to limit their reproductive investment (Parker 2000). However, empirical studies have provided conflicting evidence for the ability of males to alter their reproductive effort based on female relatedness (Pizzari et al 2004;Simmons & Thomas 2008;Lewis & Wedell 2009). Moreover, inbreeding avoidance strategies are more likely to evolve in the sex that endures the greatest cost (Zeh & Zeh 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms of post-copulatory process, such as cryptic female choice and sperm competition, will increase or decrease the degree of inbreeding (Jennions & Petrie 2000). On the other hand, Simmons & Thomas (2008) also showed that males of the cricket species Teleogryllus oceanicus do not exhibit a post-copulatory response to inbreeding. Furthermore, female E. postfasciatus are polyandrous (Sato & Kohama 2007).…”
Section: Discussionmentioning
confidence: 99%